The Development of the Impact of Early Childhood Caries on the Quality of Life of Children aged 3-5 Years at Paedodonti RSGM Baiturrahmah - Sri pandu utami Pandu; Febri liza; Hamdy Lisfrizal (Denta Journal Kedokteran Gigi, 2021)
Background: The improvement of oral health should be started as early as possible, because in toddlers and preschool children is an important factor for further regulation. dentition. In addition, it also affects the children's ability to speak and their mastery. Efforts to develop the prevention and management of dental caries continue in many countries. Currently, the prevention and management of dental caries has shown positive and dynamic aspects. However, the problem of dental caries still shows a high prevalence, especially in developing countries. Purpose: The aim of this study was to determine the impact of early childhood caries on quality of life children aged 3 - 5 years based on characteristics in pedodontics, RSGM Baiturrahmah. Material and Methods: The purpose of this study was to determine the impact of early childhood caries on the quality of life of children aged 3-5 years based on the characteristics of the pedodontics in Baiturrahmah Hospital. This type of research is quantitative with validity and reliability testing followed by quantitative methods with cross sectional research design. The population was pediatric patients who visited Paedodonti RSGM Baiturrahmah from January to February 2020. Sampling in this study used a total sampling method. In this research, Data collection was carried out by means of researchers giving questionnaires to respondents through the Google Form application. The research was conducted by using a questionnaire or questionnaire method, it is necessary to test the validity. Test the Pearson correlation using the product moment the principle of correlating or linking between each item score or question with the total score obtained from the respondent's answer or questionnaire. Results: Based on the “correlations” output, it is known that the calculated r value (Pearson correlation value for  all of question  with total score is > 0,218). all of question is valid. Conclusion: the conclusion of this study caries has an impact on early childhood development on the quality of life of children aged 3-5 years in paedodontics RSGM Baiturrahmah.